Characteristics of churn and annular flows in a large diameter vertical riser. (April 2019) - Abdulkadir, M.; Mbalisigwe, U.P.; Zhao, D.; Hernandez-Perez, V.; Azzopardi, B.J.; Tahir, S.
Highlights: New data for churn–annular flow using conductance probes placed at 3 entrance lengths are reported. The comparison between the frequency obtained from conductance probes and wire mesh sensor (WMS) showed good agreement. The comparison between the liquid film thickness obtained from conductance probes and local film thickness probes showed good agreement. The experimental data have good agreements with empirical models. Abstract: This paper presents the results of a series of experimental studies conducted to investigate the characteristics of churn and annular flows in an 11 m long riser with the internal diameter of 127 mm. A series of experiments in churn–annular flow regime were performed for a range of gas superficial velocities (3.5–16.1 m/s) and liquid superficial velocities of 0.02–0.33 m/s. Statistical analysis involving average, standard deviation and skewness, dominant frequency and structure velocity of the time series data was carried out as a quantitative approach to discriminate between churn and annular flows and to describe the transition between them. The variation of average liquid film thickness against gas superficial velocity showed a minimum at gas superficial velocity of 12.4 m/s. This is in close agreement with the minima at gas superficial velocity of 13 m/s reported in the literature. The results of the comparison between average liquid film thicknesses from the conductance ring probes agree well with those obtained by using local liquid film thickness probes and conductance ring probes in the literature. The results of the comparison of dominant frequency obtained from the conductance ring probes agree well with those obtained by using wire mesh sensor (WMS) in the literature. A comparative analysis of the current experimental data with those previously published experimental results confirms good agreement.